Evaluation of patients with cervical spine injury and predicting the risk and severity of acute spinal cord injury after a minor trauma - Maloth, Ramdas (International Journal of Research in Orthopaedics, 2020)
Background: Acute spinal cord injury (SCI) after a minor trauma to the cervical spine has been reported in patients without preceding neurologic symptoms. Spinal canal stenosis may be the reason for the discrepancy between the severity of the injury and that of the trauma. The objective of this study was to investigate MRI parameters of the cervical spine in patients suffering from acute SCI and to investigate the use of these parameters for predicting the risk and severity of acute cervical SCI after a minor trauma to the cervical spine. Methods: Retrospective radiological study was conducted in Meenakshi Medical College and Research Institute Kanchipuram with fifty patients suffering from acute cervical SCI and 130 patients showing no neurologic deficits after a minor trauma to the cervical spine. The following calculations were performed using measurements from MR images the spinal canal to vertebral body ratio, the space available for the cord, and the canal-to-cord ratio. SPSS version 21 was used for analysis. Results: All investigated MR image parameters in the SCI group were significantly (p<001) smaller compared with the control group. However, there was no significant difference in any parameter among the different American spinal injury association impairment score groups. A cut-off value of 8.0 mm for the minimal sagittal disc-level canal diameter yielded the largest positive predictive value and likelihood ratio for predicting SCI. Conclusions: Patients at risk of acute SCI after a minor trauma to the cervical spine can be identified by applying a disc-level canal diameter cut-off value measured on MR images. Supplementary factors to the radiological characteristics of the spinal canal affect the severity of acute SCI after trauma.